Membangun Kepercayaan: Relevansi Kerahasiaan dalam Mengatasi Masalah Trust Issue pada Konseling Kelompok - Ardila, Putri; Khairunnisa, Iqlima Rahma; Tazkia, Dirham Alkayyisa Tayyara; Musthofa, Muhammad Ariq; Najjini, Sabrina Luthfia; Nasution, Lusy Amelia; Nadhirah, Nadia Aulia (CV. ITTC INDONESIA, 2024)
Students' trust in guidance and counseling teachers is an important factor in determining their interest in participating in counseling services, especially group counseling. However, it is still often found that students lack trust in guidance and counseling teachers which results in students' lack of interest in participating in counseling services. Therefore, the principle of confidentiality needs to be implemented so as to build students' trust in the guidance and counseling teacher. The aim of this research is to analyze the relationship between the principle of confidentiality and students' trust in providing group counseling services. The method used in this research is a quantitative descriptive method, data collection is obtained from data collection using instruments. This research aims to build students' trust in guidance and counseling teachers, so that students will be more open in dealing with their personal problems and can optimize benefits. The results of the analysis show that the majority of respondents strongly disagree with the view that confidentiality is not important in group counseling. Most BK teachers agree that the principle of confidentiality is very important. However, there are still many guidance counselors who consider it unimportant, giving rise to students' lack of trust in guidance counselors when providing group counseling services. These findings emphasize the importance of implementing the principle of confidentiality in group counseling practices, both between guidance counselors and students and between students and students. However, the findings also highlight that there are a number of guidance and counseling teachers who do not prioritize confidentiality aspects in group counseling practices.